2020
DOI: 10.3389/fnins.2020.00622
|View full text |Cite
|
Sign up to set email alerts
|

Improved Visualization of Focal Cortical Dysplasia With Surface-Based Multiparametric Quantitative MRI

Abstract: Detection of FCD With qMRI Conclusion: Synthetically enhanced FLAIR-anatomies resulting from surface-based multiparametric qMRI-analyses have the potential to improve the visualization of FCD and, accordingly, the treatment of the respective patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Surface-based (SBM) tools at least theoretically allow for a better analysis of the cortical layers itself; however, the superiority to VBM has not been shown yet [ 20 30 , 51 , 65 ]. Multiple stand-alone tools also processing multiple including quantitative sequences are currently being developed [ 25 , 27 , 28 , 30 , 31 , 47 , 52 , 64 , 66 ]. Which postprocessing tool will prevail is at the end also a matter of availability and ease of use [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface-based (SBM) tools at least theoretically allow for a better analysis of the cortical layers itself; however, the superiority to VBM has not been shown yet [ 20 30 , 51 , 65 ]. Multiple stand-alone tools also processing multiple including quantitative sequences are currently being developed [ 25 , 27 , 28 , 30 , 31 , 47 , 52 , 64 , 66 ]. Which postprocessing tool will prevail is at the end also a matter of availability and ease of use [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acquired signals from a single ≈ 12 min 3D sequence with variable combinations of hundreds to thousands of TRs and flip angles are compared with those in a dictionary that contains signal evolutions from a wide range of physiologically relevant combinations of T1 and T2 [49). The acquired signal from each voxel is then assigned to the entry in the dictionary that best matches the signal evolution [47]. 3D MRF was reported to show additional information in 4 of 15 patients with FCD but is not in clinical routine yet [48].…”
Section: Quantitative Mri Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nöth et al ( 36 ) developed a method for improved FCD visualization, utilizing quantitative T1 maps, and assessing the cortical extent and the smoothness of the WM-GM-junction. Furthermore, a different method for improved FCD visualization based on multiparametric qMRI data (T1, T2, and PD maps) and surface-based analysis techniques has been proposed, measuring the standard deviations of the respective parameters at the WM-cortex junction ( 37 ). The resulting information on junction smoothness and additional measures of the local cortical thickness are then used in combination to artificially enhance the signal in conventional fluid attenuated inversion recovery (FLAIR) datasets, thus highlighting regions suspicious of FCD.…”
Section: Multiparametric Qmri Applications In Epilepsymentioning
confidence: 99%
“…Significant deviations of parameters from normal control values reflect tissue alterations, facilitating the identification of brain pathologies [4]. For example, it has been demonstrated that synthetic data sets derived from qMRI maps may improve the visibility of brain structures such as the deep cerebellar nuclei [5] and pathologies such as brain tumors [6] or focal cortical dysplasia [7,8]. In glioblastoma, maps of quantitative T1-relaxation time differences pre-to-post intravenous application of a gadolinium-based contrast agent (GBCA) have been shown to better visualize GBCA leakage than conventional T1-weighted MRI, indicating tumor cell infiltration in and beyond the peritumoral edema [9,10].…”
Section: Introductionmentioning
confidence: 99%